An Empirical Study on Dispute Resolution Methods (DRM) from the Perspective of Employee and Employer: Special Emphasis on Alternative Dispute Resolution (ADR) (Journal of Business and Technology (Dhaka), 2014)
In recent times, most of the parties involved in dispute resolution process are favoring Alternative Dispute Resolution or ADR over the formal adjudication process due to ADRs distinguished benefits. In order to reduce the backlog and pressure of workload, courts randomly select alternative ways to settle dispute. Therefore, a question can be raised how well ADR is working in reality? If a dispute is in existence between a company and an individual, the individual might not get a proper redress against an esteemed company. Moreover, there is a possibility of bias in favor of those who is in the superior positions. Though it was a courageous effort from the legislature and the judiciary to make the dispute resolution system compatible with the changing society, a question remains: how much upshot is there in the legal field? To what extent does the ADR process elude or ensure justice? DOI: http://dx.doi.org/10.3329/jbt.v8i1-2.18283 Journal of Business and Technology (Dhaka) Vol.8(1-2) 2013; 1-16